I wish someone had told me [compact disc, unabridged] - Perino, Dana (HarperCollins Publishers, 2025)
An all-star line-up of Dana Perino's lifelong friends and Fox News personalities with wide-ranging talents and accomplishments share amazing stories about their own experiences, offering invaluable guidance and wisdom on a range of subjects. Dana's illuminating and essential book is ideal for new graduates and everyone starting their first job; professionals thinking about making a change, transitioning into a different position, or phasing into a new career or act in life; and anyone looking for timeless insight and a helpful resource for self-improvement and career enhancement.